2000
DOI: 10.1074/jbc.275.17.13071
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Platelet Receptor-mediated Factor VIII Binding

Abstract: The importance of factor VIII (FVIII) 1 and FIX in hemostatic reactions is evident by the fact that hemophilia A (FVIII deficiency) and hemophilia B (FIX deficiency) are the two most serious congenital coagulation defects, both producing severe, life-threatening and life-long hemorrhagic disease. FVIII is synthesized as a single polypeptide chain containing 2,351 amino acids (1) and shows a discrete domain structure, A1-a1-A2-a2-B-a3-A3-C1-C2; the domains are separated by short spacers (a1, a2, and a3) compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
95
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(108 citation statements)
references
References 81 publications
11
95
1
1
Order By: Relevance
“…This C1C2 binding was only partially competed by FVIII or FVIIIa. Fluorescein-labeled FVIII and FVIIIa did not bind to platelets before activation, as reported by others, 19,36,37 so this observed C1C2 binding is unlikely to be physiologically relevant. However, Nesheim et al 38 reported 450 binding sites per activated platelet for 35 S-Met-labeled FVIII and approximately 20 FVIII molecules bound per nonactivated platelet.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…This C1C2 binding was only partially competed by FVIII or FVIIIa. Fluorescein-labeled FVIII and FVIIIa did not bind to platelets before activation, as reported by others, 19,36,37 so this observed C1C2 binding is unlikely to be physiologically relevant. However, Nesheim et al 38 reported 450 binding sites per activated platelet for 35 S-Met-labeled FVIII and approximately 20 FVIII molecules bound per nonactivated platelet.…”
Section: Discussionsupporting
confidence: 72%
“…42 The estimate of 7000 C1C2-binding sites per activated platelet ( Figure 7) was 4-to 5-fold greater than the 1400 sites estimated for C2. Previous estimates of FVIIIa molecules bound to activated platelets have ranged from 200 to 2000 molecules bound per platelet, 10,19,37,38,43 although higher estimates of up to approximately 25 000 sites per activated platelet have also been reported. [42][43][44][45] Different methods of activating the platelets might account for some of this variation, and heterogeneity in the activated platelet population can also complicate analysis of binding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FVIII (K d ~3.0 nM) (4,9,10) and FVIIIa (K d ~0.8 nM) (4) also bind to specific, high-affinity sites on activated platelets. Although FX and prothrombin occupy a high-capacity, low-affinity (K d ~300 nM) shared site (5), FX also occupies a specific binding site (K d ~5 nM), consisting of bound FVIIIa (4,6,11).…”
mentioning
confidence: 99%